2009
DOI: 10.1093/intimm/dxp069
|View full text |Cite
|
Sign up to set email alerts
|

A functional soluble form of CTLA-4 is present in the serum of celiac patients and correlates with mucosal injury

Abstract: Celiac disease (CD) is a multifactorial disorder influenced by environmental, genetic and immunological factors. Increasing evidence showed CTLA-4 gene as an important susceptibility locus for autoimmune disorders. A native soluble cytotoxic T-lymphocyte-associated protein-4 (sCTLA-4), lacking of transmembrane sequence, has been described in several autoimmune diseases. We aimed to evaluate the presence of increased sCTLA-4 concentration in the serum of patients with CD and the possible immunoregulatory functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 44 publications
4
61
0
Order By: Relevance
“…A comparison of these results with those obtained in 85 patients with CD in remission on a gluten-free diet showed that sCTLA-4 concentrations are related to gluten intake. A correlation between autoantibodies to tissue transglutaminase or the degree of mucosal damage and sCTLA-4 concentrations h also been found [51]. In addition, we have observed that serum sCTLA-4 is able to downregulate the proliferative ability of T lymphocytes in vitro [51].…”
Section: Sctla-4 and Autoimmune Diseasesmentioning
confidence: 64%
See 4 more Smart Citations
“…A comparison of these results with those obtained in 85 patients with CD in remission on a gluten-free diet showed that sCTLA-4 concentrations are related to gluten intake. A correlation between autoantibodies to tissue transglutaminase or the degree of mucosal damage and sCTLA-4 concentrations h also been found [51]. In addition, we have observed that serum sCTLA-4 is able to downregulate the proliferative ability of T lymphocytes in vitro [51].…”
Section: Sctla-4 and Autoimmune Diseasesmentioning
confidence: 64%
“…More recently, we found an increased in sCTLA-4 levels in the serum of patients with untreated CD (in 54 out of 75 CD patients; range 0.1-96.4 ng/ml), and analysed its possible immunoregulatory function [51]. A comparison of these results with those obtained in 85 patients with CD in remission on a gluten-free diet showed that sCTLA-4 concentrations are related to gluten intake.…”
Section: Sctla-4 and Autoimmune Diseasesmentioning
confidence: 86%
See 3 more Smart Citations